How Financial Literacy and Investment Knowledge Influence Gold Investment Decisions - Sugiastuti, Reika Happy; Friseyla, Vhallensya; Pramesti, Regita (Profit: Jurnal Adminsitrasi Bisnis, 2024)
This research investigates the impact of financial literacy and investment knowledge on gold investment decisions among 30 members of the EOA Gold community in Malang, covering Batu City, Malang City, and Malang Regency. Data collected through surveys and questionnaires were analyzed using multiple linear regression in IBM SPSS version 29. The findings indicate that while financial literacy alone does not significantly influence gold investment decisions, investment knowledge plays a crucial role. Moreover, financial literacy and investment knowledge significantly affect these decisions when considered together. These results underscore the importance of enhancing investment knowledge among investors to make informed decisions about gold investments. The implications suggest that targeted educational programs and strategies focusing on investment knowledge could improve financial decision-making outcomes in gold investments.